Neurogenic niches in the brain: help and hindrance of the barrier systems - Stolp, Helen B.; Molnár, Zoltán (Frontiers in Neuroscience, 2015)
In the developing central nervous system, most neurogenesis occurs in the ventricular and subventricular proliferative zones. In the adult telencephalon, neurogenesis contracts to the subependyma zone and the dentate gyrus (subgranular zone) of the hippocampus. These restricted niches containing progenitor cells which divide to produce neurons or glia, depending on the intrinsic and environmental cues. Neurogenic niches are characterised by a comparatively high vascular density and, in many cases, interaction with the cerebrospinal fluid (CSF). Both the vasculature and the CSF represent a source of signalling molecules, which can be relatively rapidly modulated by external factors and circulated through the central nervous system. As the brain develops, there is vascular remodelling and a compartmentalisation and dynamic modification of the ventricular surface which may be responsible for the change in the proliferative properties. This review will explore the relationship between progenitor cells and the developing vascular and ventricular space. In particular the signalling systems employed to control proliferation, and the consequence of abnormal vascular or ventricular development on growth of the telencephalon. It will also discuss the potential significance of the barriers at the vascular and ventricular junctions in the influence of the proliferative niches.